Effect of Irrigation with Treated Municipal Wastewater on Vitis vinifera L. cvs. Cabernet Sauvignon and Sauvignon blanc in Commercial Vineyards in the Coastal Region of South Africa - Vegetative Growth, Yield and Juice Characteristics - Hoogendijk, K.; Myburgh, P.A.; Howell, C.L.; Lategan, E.L.; Hoffman, J.E. (South African Journal of Enology and Viticulture, 2023)
A long-term trial was conducted in commercial vineyards in the Coastal region of South Africa to assess the impact of treated municipal wastewater irrigation on vineyards. Cabernet Sauvignon and Sauvignon blanc grapevines were irrigated using treated municipal wastewater from the Potsdam wastewater treatment works for 11 years. Grapevines were either rainfed (RF), irrigated with treated municipal wastewater via a single dripper line (SLD) or received twice the volume of wastewater via a double dripper line (DLD). Grapevine responses were measured from the 2013/14 to 2017/18 seasons. Although high amounts of K+, Na+ and Cl- were applied via wastewater irrigation, it did not result in excessive uptake by plants and did not affect vegetative growth or yield negatively. Irrigation reduced water constraints throughout the growing season compared to RF conditions, particularly for Cabernet Sauvignon. Consequently, SLD and DLD grapevines produced stronger vegetative growth and higher yields compared to RF. Results showed that the availability of irrigation water (albeit of relatively low quality) in regions where grapevines are usually grown under dryland conditions can increase grapevine productivity whilst maintaining good fruit quality. However, the water can vary in its availability as well as its quality over a short period of time. Plant and soil water status should be monitored regularly to avoid over-irrigation. Implementing low frequency irrigation scheduling with a sufficient leaching fraction will allow adequate time between irrigation applications for soils to aerate and organic material to decompose. Irrigation water, soils and grapevine leaves should be analysed to ensure that chemical parameters conform to recommended thresholds and norms.